2004
DOI: 10.1126/science.1094070
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Earth's Reflectance over the Past Two Decades

Abstract: We correlate an overlapping period of earthshine measurements of Earth's reflectance (from 1999 through mid-2001) with satellite observations of global cloud properties to construct from the latter a proxy measure of Earth's global shortwave reflectance. This proxy shows a steady decrease in Earth's reflectance from 1984 to 2000, with a strong climatologically significant drop after 1995. From 2001 to 2003, only earthshine data are available, and they indicate a complete reversal of the decline. Understanding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
87
1
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(95 citation statements)
references
References 6 publications
6
87
1
1
Order By: Relevance
“…It is noticeable, however, that over the 1960-1984 period there is a general decrease in bright sunshine hours (a surface dimming), followed by a recovery from the mid-1980s till the present. These changes are consistent with the so-called 'global dimming' phenomena observed at other ground-based observatories worldwide from the 1960s to the mid1980s (Stanhill and Cohen, 2001;Liepert, 2002) and the 'global brightening' that followed, starting in the mid1980s (Pallé et al, 2004;Wild et al, 2005). Seasonal trends in sunshine hours are detailed in Table I. 3.2.…”
Section: Synoptic Cloud Observations At Ebrosupporting
confidence: 70%
“…It is noticeable, however, that over the 1960-1984 period there is a general decrease in bright sunshine hours (a surface dimming), followed by a recovery from the mid-1980s till the present. These changes are consistent with the so-called 'global dimming' phenomena observed at other ground-based observatories worldwide from the 1960s to the mid1980s (Stanhill and Cohen, 2001;Liepert, 2002) and the 'global brightening' that followed, starting in the mid1980s (Pallé et al, 2004;Wild et al, 2005). Seasonal trends in sunshine hours are detailed in Table I. 3.2.…”
Section: Synoptic Cloud Observations At Ebrosupporting
confidence: 70%
“…Observations of earthshine for example, have shown that clouds can induce a considerable daily variation A&A 548, A90 (2012) in the planetary signal. The amount of variability observed differs slightly among the observations (∼10% for Pallé et al 2004; ∼5% for Goode et al 2001, and a few percent for Cowan et al 2009). Cloud coverage and variability can also influence to a large degree the interpretation of the observations.…”
Section: Introductionmentioning
confidence: 79%
“…The issue has arisen because of apparent inconsistencies among direct and indirect observational records of the Earth's reflected solar radiation. While Pallé et al [2004] looked at Earthshine data and found a steady decrease in the Earth's broadband reflectance from 1984 to 2000 followed by an increase between 2001, Wielicki et al [2005 found no trend in planetary broadband albedo from an analysis of CERES data coupled with other correlative satellite records from the Moderate Resolution Imaging Spectrometer (MODIS) [Justice et al, 1998] and Jason/TOPEX [Ducet et al, 2000]. This debate and additional problems encountered by researchers attempting to synthesize long-term climate records by harmonizing heterogeneous satellite instrument data [i.e., Hurrell and Trenberth, 1998] have led to the recognition of the critical importance of long-term measurement stability that is rigorously traceable to international standards for the assessment of changes in climate.…”
Section: Introductionmentioning
confidence: 99%